Identificações e recepção: o olhar dos moradores do bairro Pantanal ou Planalto Ayrton Senna sobre o vídeo popular da TV Janela - Braga, Robson da Silva (2010)
This study revealed how five selected recipients (viewers) of the “Window TV” videos identified with the positive representations about the "resident of Pantanal" (a community originated in 1990, in the southern outskirts of Fortaleza - CE), presented in the audiovisual productions created under a project from the NGO Institute for Social Development (IDS). The videos of the project show, in general, a participative, hardworking resident, committed to a cause and therefore, victorious and happy, as opposed to the fictional violence and misery built by the mainstream media about the location. The goal of the “Window TV” is to improve the self-esteem of some three hundred people who watch the videos monthly on a screen set up on the street. The research aimed to understand a particular stage of the communication process (reception) through the concepts of the community, social representations and cultural identification. It has a qualitative dimension, and used the ethnography and in-depth interview as a methodological procedure; the Discourse analysis as a method of discourse analysis of the selected recipients and Cultural Studies as a theoretical perspective. Aspects such as the time in which the viewers arrived at the neighborhood, their life history and daily interactions with the community and its dwellers interfere with their identity building as a resident of the Pantanal and consequently, in the way they appropriate the representations of a resident presented by video. Even the more emphasized aspects brought by the videos, such as the fight history, can only get support from the receivers when they have themselves experienced the specific fact or learned it previously with the older residents, their living together with the community or family.